Smartphone purchasing behavior among generation Y students in UiTM Sarawak / Norsila Sudin - Sudin, Norsila (2015)
According to Gartner, Inc. (NYSE: IT), “worldwide combined shipments of devices such as PC’s, tablets, and mobile phones are projected to reach 2.5 billion units in 2014, which 6.9 percent increase from 2013.” it shows that the demand for gadgets will increase from year to year. One ofthe reasons behind this is due to the fast changes in the technological development in market such as mobile commerce which is the trend worldwide nowadays (Kalatoka & Robinson, 2001; Liang & Wei, 2004).